A study on the effect of temperature and micro- nutrients in biogas production by dry anaerobic digestion of municipal solid waste (Chemical Engineering Research Bulletin, 2026)
Energy scarcity is soaring due to the over exploitation of fossil fuel reserves in Bangladesh. On the contrary, a potential energy source i.e. organic municipal solid waste is creating a serious environmental hazard for municipalities ascribe to ineffective and commercially unviable waste management strategy. Therefore, the present study was performed on a dry anaerobic digestion process for biogas production from unsorted organic municipal solid waste. In batch digesters with a 5L effective capacity, the performance of the dry anaerobic digestion (DAD) process of solid waste was assessed during the period of 35 days of operation. Different factors i.e. temperature (35°C, 40°C, and 45°C), micro-nutrients (Na+, K+, Co+) and inoculum mixing ratio (Anaerobic sludge: Cow manure = 1:2, 1:3 and 2:1) were analyzed to observe the biogas production. The results show that biogas production was comparatively higher (approx. 375 mL/day) for 35°C where anaerobic sludge (AS) to cow manure (CS) ratio more than 1. The obtained gas composition was analyzed further to compare the biomethane production depending on these factors. A machine learning (ML) algorithm i.e. Random Forest Regressor was implemented to predict the biogas generation considering different parameters. The model showed performance with more than 77.8% accuracy (R-squared value). Future research can be performed by conducting experiments considering other factors which affects biogas generation and a better model can be implemented to predict the nature of biomethane production.Chemical Engineering Research Bulletin: 24 (Issue 1): 20-29